THE RELATIONSHIP OF MORPHOLOGICAL CHARACTERISTICS WITH THE PERFORMANCE OF THE TECHNIQUE OF THROWING WITH THE STANDING LEG LEFT FROM THE BACK - Darko Paspalj,; Nenad Rađević,; Lazar Vulin,; Saša Kovačević, (Sport Scientific And Practical Aspects, 2025)
The aim of the work was to determine the connection between morphological characteristics and the effectiveness of the throwing technique by kicking the legs from behind from the program of Special Physical Education (SPE). The sample of respondents consisted of 84 students (male), first year of the Faculty of Security Sciences from Banja Luka. The variable sample was composed of 17 tests for the evaluation of morphological characteristics, which were the independent variables and the dependent variable OSOTOG, which was the average grade of the performance of the kicking technique from the SPE program. The regression analysis did not establish a statistically significant connection between the efficiency of performing the throwing technique by striking the landing leg from behind and the selected set of predictor variables for the assessment of morphological characteristics. Only the elbow diameter variable (ADIJLA) gave a statistically significant contribution to the explanation of the criteria variable OSOTOG. Based on the value of the Beta coefficients, we can see that the variables: body weight (ATETJ) and leg length (ADUZNO) have significant positive partial correlations with the criterion variable, while negative correlations were achieved by the variables: elbow diameter (ADIJLA), body height (AVISTJ) and length hands (ADUZRU). The obtained results could be used in terms of improving the quality of the performance of certain program contents of the SPE, when choosing the appropriate technique within the motor program when solving certain problem situations from the SPE program.